Pendidikan Kewarganegaraan dan Hak Asasi Manusia : Membentuk Kesadaran Warga Negara yang Bertanggung Jawab - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Lintang Indah Meilasari; Shafanisa Ganefiaida Rizky Suharto; Angelica Alyscha Ocktaviona (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
For citizens who support democracy, ethics and human rights (HAM), civic education is an important instrument to shape their character and mentality. In the era of globalization and openness of information, the value of education which places a strong emphasis on strengthening human rights (HAM) values is very important. The design of civic awareness for theoretical approaches and literature research may actively involve the formation of citizenship, as discussed in this paper. This article examines the application of incorporating human rights (HAM) ideals into civic education instruction in educational settings using a descriptive qualitative approach. Civic education is an important instrument in shaping the character and mindset of citizens who uphold democracy, ethics and human rights (HAM). The political consequences of this research include the need for curriculum renewal, institutional support, teacher training and the idea that civic learning is a process rather than a means to achieve civic and human ideals.